Antimicrobial Resistance of F4+ Escherichia Coli Isolated from Swine in Italy. Issue 1 (21st March 2013) - Luppi, A.; Bonilauri, P.; Dottori, M.; Gherpelli, Y.; Biasi, G.; Merialdi, G.; Maioli, G.; Martelli, P.
Summary Four‐hundred and forty‐two F4+ pathogenic Escherichia coli were isolated in a period of 10 years (2002–2011), from pigs that were suffering from diarrhoea belonging to Italian swine herds. The strains were analysed for their susceptibility to 12 antimicrobials using the disc diffusion method. During the study period, a statistically significant proportion of isolates resistant to enrofloxacin (14.5–89.3%), marbofloxacin (5.4–60.7%), flumequine (49.1–92.9%), danofloxacin (21.6–80%), florfenicol (9.8–64.3%), thiamphenicol (50–92%) and cefquinome (3.8–44%) was recorded. An increase in resistance (not statistically significant) to gentamicin (63.6–85.7%), apramycin (61.8–82.1%), trimethoprim‐sulphamethoxazole (75–89.3%), tetracycline (97–100%) and erythromycin (92.4–100%) was also observed. Based on antimicrobial multiresistance, the strains were collected into three groups: I. resistant to 2–5 antimicrobials; II. resistant to 6–8 antimicrobials; III. resistant to 9–12 antimicrobials. The number of isolates belonging to the first group showed a statistically significant decrease (P < 0.05; R2 = 0.896; r = −0.9608), while the isolates belonging to the second and third groups showed a statistically significant increase in resistance (P < 0.05; R2 = 0.753; r = 0.8890 and P < 0.05; R2 = 0.727; r = 0.8701, respectively) over the period of study. The results of this study suggest the need for continued monitoring of the development of resistance.